A simple method for determining critical speed as swimming fatigue threshold in competitive swimming - Wakayoshi, K.; Yoshida, T.; Udo, M.; Kasai, T.; Moritani, T.; Mutoh, T.; Miyashita, M. (International Journal of Sports Medicine, 1992)
Critical swimming speed is a theoretical velocity that could be maintained continuously without exhaustion. It is determined by swimming several distances at maximum speeds so that a regression line between swimming distance and time can be obtained. The slope of the regression line is used to indicate the critical speed. In this investigation highly trained swimmers (N = 8) were instructed to swim until fatigue at four predetermined speeds in a swimming flume and over four different distances (50, 100, 200, and 400 m) in a pool. The critical speeds for flume swimming and pool swimming were determined. VO2max, swimming velocity related to the accumulation of 4 mM lactate (V-OBLA), and average 400 m crawl stroke velocity were also determined. Significant correlations between various factors were found. However, there were some interesting results that have implications for coaches. 1.The correlation between critical speeds in the flume and pool was .824, indicating that the two tasks were 68% related. This means that there are considerable differences between flume and pool swimming. They are of such magnitude that flume data should not be applied directly to pool work. 2.Critical speed in the pool was very highly related (r = .998) to 400-m velocity while flume critical velocity was correlated lower (not as highly related). 3.VO2max was not related significantly to any other variable. 4.The relationships of V-OBLA and critical speeds for both flume and pool swimming were lower than those of critical speed in the pool and 400-m velocity. Implication: While tests of critical speeds in flumes and measures of physiological parameters and their corresponding swimming velocities are popular in research and among "swimming scientists" they offer less reliable and predictive information than work in the pool. In this investigation it was shown that tests in the pool predicted actual 400-m swimming velocity better than tests in a flume. One is set to wonder whether a swimming flume is worth the expense associated with its construction. Swimming in a flume is a different activity to swimming in a pool.